FEEDBACK: DIFFERENT CONCEPTS AND PRACTICES IN A CULTURALLY DIFFERENT LEARNING ENVIRONMENT? STUDENTS’ PERCEPTIONS - Ahsan Malik (Army Medical College Rawalpindi, 2021)
Objective: To assess students’ perceptions of feedback, regarding its understanding, and practices in a traditional undergraduate dental curriculum in Pakistan, where feedback was not part of a formal curriculum as a structured entity.